Predominately Uncultured Microbes as Sources of Bioactive Agents - Newman, David J. (Frontiers in Microbiology, 2016)
In this short review, I am discussing the relatively recent awareness of the role of symbionts in plant, marine and fungal areas. It is now quite obvious that in the marine area, a majority of compounds found are from either as yet unculturable or poorly culturable microbes, and techniques involving “state of the art” genomic analyses and subsequent computerized analyses are required to investigate these interactions. In the plant kingdom evidence is amassing that endophytes (mainly fungal in nature) are heavily involved in secondary metabolite production and that mimicking the microbial interactions of fermentable microbes leads to involvement of previously unrecognized gene clusters (cryptic clusters is one name used), that when activated, produce previously unknown bioactive molecules.